Resource concentration dilutes a key pest in indigenous potato agriculture - Parsa, S; Ccanto, Raul I.; Rosenheim, Jay A. (Wiley, 2011)
Modern restructuring of agricultural landscapes, due to the expansion of monocultures and the resulting elimination of non-crop habitat, is routinely blamed for rising populations of agricultural insect pests. However, landscape studies demonstrating a positive correlation between pest densities and the spatial extent of crop monocultures are rare. We test this hypothesis with a data set from 140 subsistence farms in the Andes and find the inverse correlation. Infestations by the Andean potato weevil (Premnotrypes spp.), the most important pest in Andean potato agriculture, decrease with increasing amounts of potato in the landscape. A statistical model predicts that aggregating potato fields may outperform the management of Andean potato weevils by IPM and chemical control. We speculate that the strong pest suppression generated by aggregating potato fields may partly explain why indigenous potato farmers cluster their potato fields under a traditional rotation system common in Andean agriculture (i.e., “sectoral fallow”). Our results suggest that some agricultural pests may also respond negatively to the expansion of monocultures, and that manipulating the spatial arrangement of host crops may offer an important tool for some IPM programs.